ANIMASI ANAK NUSSA DAN RARA DI YOUTUBE (ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE) (Fakultas Dakwah dan Komunikasi, 2020)
This study examines the value of film animated child Nussa and Rara on Youtube (semiotic analysis of Ferdinand de Saussure). This aims to: How the meaning of the markers related to the moral messages contained in the animation children of Nussa and Rara on Youtube. The results of this study indicate that the animation of the Nussa and Rara children has positive messages both linguistic and non-linguistic which can be seen from several episodes containing markers of moral messages including moral messages to oneself include learning to be sincere or history, always being enthusiastic and not giving up, loving animals and always being grateful. Moral messages to others include warm-heartedness, sharing with others, friendship, doing good to neighbors, giving alms, and forgiveness.